Probability Analysis of Overtopping During Construction Period of Dam Based on Improved Interval Non-Probabilistic Reliability - Xinyan Guo; Zongkun Li; Wei Ge; Fuheng Ma; Yadong Zhang; Heqiang Sun; Yutie Jiao; Jianyou Wang (Applied Sciences, 2025)
Probabilistic analysis of overtopping is an important aspect of dam construction, and the uncertainty in the construction progress complicates the calculation of overtopping probabilities. Construction progress is significantly influenced by human factors, making it difficult to assign an accurate probability distribution. Although the interval non-probabilistic reliability (INPR) method can estimate the likelihood of events with unknown probability distributions, its calculation results for the overtopping probability have significant errors. To improve the rationality of the results, we developed a method that adopted flood frequency of the upstream flood level to correct the traditional INPR calculations, developing an improved model. Taking the Qianping Reservoir as an example, the overtopping probabilities for three construction schedules were calculated, and the results were compared with a flood routing calculation. The results indicated that the improved approach significantly improves the rationality of the calculations, and the results effectively reflected the impact of construction progress uncertainty on overtopping probabilities.